2006
DOI: 10.1097/01.yic.0000182116.49887.ae
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine as an adjunctive treatment for post-traumatic stress disorder: an 8-week open-label study

Abstract: This study evaluated the effectiveness of quetiapine for subjects with post-traumatic stress disorder (PTSD) who were already on a stable dose of a selective serotonin reuptake inhibitor (SSRI) but had significant PTSD symptoms. Fifteen subjects were enrolled in an 8-week open-label trial for PTSD in which quetiapine was added to an SSRI. Subjects were on a stable dose of the SSRI for at least 6 weeks before study entry and had a Clincian-Administered PTSD Scale (CAPS) score of greater than or equal to 50 at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…The empirical literature is dominated by case studies/series, nonrandomized, and non-placebo-controlled studies on the use of quetiapine (Ahearn, Mussey, Johnson, Krohn, & Krahn, 2006;Filteau, Leblanc, & Bouchard, 2003;Robert et al, 2005;Hamner, Deitsch, Brodrick, Ulmer, & Lorberbaum, 2003;Sokolski, Denson, Lee, & Reist, 2003;Stathis, Martin, & McKenna, 2005), olanzapine (Butterfield, 2003;Izrayelit, 1998;Jakovljevic,Šagud, & Mihaljevic-Peleš, 2003;Labbate & Douglas, 2000;Petty, Brannan, & Casada, 2001;Pivac, Kozaric-Kovacic, & Mück-Šeler, 2004;Prior, 2001), risperidone (David, De Faria, Lapeyra, & Mellman, 2004;David, De Faria, & Mellman, 2006;Kozaric-Kovacic, Pivac, Mück-Šeler, & Rothbaum, 2005;Krashin & Oates, 1999;Monnelly & Ciraulo, 1999;Monnelly, Ciraulo, Knapp, & Keane, 2003), aripiprazole (Lambert, 2006), ziprasidone (Siddiqui, Marcil, Bhatia, Ramaswamy, & Petty, 2005), and clozapine (Hamner, 1996). To date, there are only a handful of published studies examining the efficacy of atypical antipsychotics utilizing a double-blind, placebo-controlled, and randomized design, and they have focused on risperidone (Bartzokis, Lu, Turner, Mintz, & Saunders, 2005;Hamner, Faldowski, et al, 2003;Monnelly et al, 2003;Reich, Winternitz, Hennen, Watts, & Stanculescu, 2004) and olanzapine (Butterfield et al, 2001;Stein, Kline, & Matloff, 2002).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…The empirical literature is dominated by case studies/series, nonrandomized, and non-placebo-controlled studies on the use of quetiapine (Ahearn, Mussey, Johnson, Krohn, & Krahn, 2006;Filteau, Leblanc, & Bouchard, 2003;Robert et al, 2005;Hamner, Deitsch, Brodrick, Ulmer, & Lorberbaum, 2003;Sokolski, Denson, Lee, & Reist, 2003;Stathis, Martin, & McKenna, 2005), olanzapine (Butterfield, 2003;Izrayelit, 1998;Jakovljevic,Šagud, & Mihaljevic-Peleš, 2003;Labbate & Douglas, 2000;Petty, Brannan, & Casada, 2001;Pivac, Kozaric-Kovacic, & Mück-Šeler, 2004;Prior, 2001), risperidone (David, De Faria, Lapeyra, & Mellman, 2004;David, De Faria, & Mellman, 2006;Kozaric-Kovacic, Pivac, Mück-Šeler, & Rothbaum, 2005;Krashin & Oates, 1999;Monnelly & Ciraulo, 1999;Monnelly, Ciraulo, Knapp, & Keane, 2003), aripiprazole (Lambert, 2006), ziprasidone (Siddiqui, Marcil, Bhatia, Ramaswamy, & Petty, 2005), and clozapine (Hamner, 1996). To date, there are only a handful of published studies examining the efficacy of atypical antipsychotics utilizing a double-blind, placebo-controlled, and randomized design, and they have focused on risperidone (Bartzokis, Lu, Turner, Mintz, & Saunders, 2005;Hamner, Faldowski, et al, 2003;Monnelly et al, 2003;Reich, Winternitz, Hennen, Watts, & Stanculescu, 2004) and olanzapine (Butterfield et al, 2001;Stein, Kline, & Matloff, 2002).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…All studies demonstrated a significant reduction in CAPS total scores and CAPS subscale scores (avoidance, re-experiencing and hyperarousal). Ahearn et al (2006) found an average final CAPS score of 46, representing a 42% decrease in symptom severity. All three subscales, B, C and D, showed significant reduction as well (23 to 10, 27 to 23 and 26 to 14, respectively).…”
Section: Quetiapinementioning
confidence: 99%
“…Quetiapine use for treating refractory PTSD is shown to be effective in three open-label trials (Ahearn, Mussey, Johnson, Krohn, & Krahn, 2006;M. B. Hamner, Deitsch, Brodrick, Ulmer, & Lorberbaum, 2003;Kozaric-Kovacic & Pivac, 2007).…”
Section: Quetiapinementioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] In one of these open studies, it was possible to identify clinical improvement in the second week of treatment. In a series of cases, 18 quetiapine was proven to be efficient to decrease flashbacks in five patients with treatment-refractory PTSD using several classes of drugs.…”
Section: 14mentioning
confidence: 99%